Working through setbacks in psychotherapy : crisis, impasse and relapse - Leiper, Rob (Sage, 2001)
Will help therapists overcome obstacles and setbacks in the successful development and maintenance of the therapeutic relationship. Drawing on a range of theoretical approaches, the authors present a framework for understanding problems that arise and offer guidance for working through them.